Diversification dynamics of Placentalia (Mammalia): integrating the fossil record with molecular phylogenies - Sugawara, Mauro Toshiro Caiuby (2015)
The effects of intrinsic traits on the diversification dynamics have been extensively investigated, with several traits being associated with increase in diversification. On the other hand, the possible negative effects of traits on the diversification of a lineage have been for the most part overlooked. Here we used both the fossil record and molecular data to study the diversification dynamics of Placentalia, focusing on the orders in decline of diversity, and investigated different mechanisms that might control the evolutionary success of the 21 placental orders. More specifically we: 1- determined which of the 21 orders of Placentalia are in decline of diversity (i.e., Decline model); 2- investigated whether the Decline model has a phylogenetic signal; 3- tested the hypothesis that the differences in body size are related to the Decline model; 4- tested the hypothesis that the orders in Decline have lower morphological disparity; 5- investigated whether the orders in decline of diversity, inferred from the fossil record, are the ones with higher extinction risk nowadays. Our analysis indicate that the majority of the orders of placental mammals have a pattern consistent with the Decline model and, although the Decline model is not equally distributed among the placental superorders, there was no significant phylogenetic signal for the orders in diversity decline. We found a positive correlation between the Decline model and the average body size which is in line with previous studies on body size evolution. We argue that such results suggest a complex evolutionary dynamics: larger body size appears to be an evolutionary attractor with lineages showing a tendency to increase in size, however, the increase in body size would be counterbalanced by a higher propensity to Decline. Moreover, we found a the negative correlation between the Decline model and morphological variation. We suggest that such results could indicate two possible scenario: (i) the low morphological variation would cause lineages to loose diversity; (ii) the low morphological variation would be the product of decrease in diversity through extinction selectivity. Finally, we found no correlation between the extinction risk of extant species and the deep time diversity decline, which suggests that the drivers of the current and the past Decline are not the same